In Silico Study of Cladosporol and Its Acyl Derivatives as Anti-Breast Cancer Against Alpha-Estrogen Receptor (Biosaintifika: Journal of Biology & Biology Education, 2024)
Breast cancer is a chronic health problem that causes 690,000 deaths worldwide. The development of secondary metabolite compounds from natural preparations through an in silico approach is needed as a predictive tool to prevent breast cancer, one of them is cladosporol from Cladosporium spp. This study aims to utilize an in silico approach to predict the potential of cladosporol against alpha-estrogen receptors. The alpha-estrogen receptor with code 6CBZ was selected based on group function as pharmacophore in ligand-receptor interaction. The methods used in this study are by using an in silico approach with Molegro Virtual Docker (MVD) Ver 5.5 for the docking process and CABS-flex 2.0 for identifying the stability of the complexes. ADMET properties analysis was also performed to know the pharmacokinetics attributes of cladosporol. Based on research conducted, stated that cladosporol octanoate has the lowest rerank score with a -84.3593 value and the RMSD value is 1.195 Å so it’s valid for molecular docking. Exploration of cladosporol for anti-breast cancer from Cladosporium spp fungi can be a novelty for the development of future pharmaceutical research. Thus, the development of anti-cancer drugs for early prevention can be carried out to reduce the number of breast cancer cases worldwide.